Multicenter randomized phase II study of cisplatin and fluorouracil plus docetaxel (DCF) compared with cisplatin and fluorouracil plus Adriamycin (ACF) as preoperative chemotherapy for resectable esophageal squamous cell carcinoma (OGSG1003). (29th September 2016) - Yamasaki, M.; Yasuda, T.; Yano, M.; Hirao, M.; Kobayashi, K.; Fujitani, K.; Tamura, S.; Kimura, Y.; Miyata, H.; Motoori, M.; Shiraishi, O.; Makino, T.; et al.
Abstract: Background: This phase II trial evaluated the efficacy of cisplatin and fluorouracil (CF)-based combination neoadjuvant chemotherapy on the outcome of patients with resectable locally advanced esophageal squamous cell carcinoma (ESCC). We compared the recurrence-free survival (RFS) associated with CF plus Adriamycin (ACF) with that associated with CF plus docetaxel (DCF) to select an alternative regimen in a new phase III trial investigating the optimal neoadjuvant treatment of patients with ESCC. Patients and methods: Patients with resectable advanced ESCC were randomly assigned to either ACF (Adriamycin 35 mg/m 2, cisplatin 70 mg/m 2 i.v. on day 1, fluorouracil 700 mg/m 2 continuous infusion for 7 days) every 4 weeks or DCF (docetaxel 70 mg/m 2, cisplatin 70 mg/m 2 i.v. on day 1, fluorouracil 700 mg/m 2 continuous infusion for 5 days) every 3 weeks. Surgery was scheduled after completion of two cycles of chemotherapy. The primary end point was RFS, analyzed by the intention-to-treat. Results: Between October 2011 and October 2013, 162 patients at 10 institutions were enrolled in the study, all of whom were eligible and randomly assigned to the two groups (81 to the ACF group and 81 to the DCF group). The R0 resection rates for the ACF and DCF groups were equivalent (95.9% versus 96.2%, P  =   0.93). The 2-year RFS and overall survival rates for DCF versus ACF were 64.1% versus 42.9% (hazard ratio 0.53, 95% confidence interval 0.33–0.83, P  = 0.0057) and 78.6% versus 65.4% ( P  = 0.08), respectively. Conclusion: Compared with ACF, DCF chemotherapy was associated with prolonged RFS for patients with resectable advanced ESCC. Thus, DCF chemotherapy has potential as a standard neoadjuvant therapy for resectable ESCC. Clinical Trial Registration: University Hospital Medical Information Network Clinical Trials Registry of Japan (identification number UMIN000004555/000004616).